Effect of sowing dates and nitrogen application on growth and productivity of canola oilseed rape (Brassica napus) (Journal of Oilseed Brassica, 2026)
A field study was conducted to observe the effect of nitrogen (N) application time on growth and productivity of canola oilseed rape (Brassica napus) under different sowing dates. Treatments comprised three sowing dates (15 October, 30 October and 15 November) allocated to main plots and seven treatments of time of application of two doses of N to sub plots in three replications. Each successive delay in sowing from 15 October to 30 October and further to 15 November significantly delayed the initiation and completion of emergence and required significantly more number of days for initiation and completion of flowering but required lesser number of days to attain physiological maturity. Each delay in sowing also caused significant reduction in plant height (except between 30 October and 15 November at maturity), dry matter, leaf area index, SPAD value at 40 and 120 days after sowing (DAS) and interception of photosynthetically active radiation at 40 and 80 DAS. Crop sown on 15 October produced 4.1% more (significantly) seed yield (2476 kg/ha) and 27.3% more (significantly) stover yield (9458 kg/ha) than 30 October sown crop, which in turn produced 36.1% and 36.4% more seed and stover yields than 15 November sown crop. Effect of dose (100 and 125 kg) and time of application (two or three splits) of nitrogen (N) on initiation or completion of emergence was inconspicuous but application of 125 kg/ha of N delayed the maturity, increased plant height (mean over time of application) at all growth stages over 100 kg/ha of N, whereas its effect on other growth parameters was variable. Application of 125 kg/ha of N resulted in 11.9% higher seed yield and 8.3% higher stover yield (mean over N application time) than that obtained with 100 kg/ha of N. Effect of time of application of N on different growth parameters (DMA, LAI, PARI, SPAD values) at different growth stages was variable. The maximum seed yield (2405 kg/ha) and stover yield (7919 kg/ha) obtained with 125 kg/ha of N applied in three splits (50 + 50 + 25) was at par with application of 125 kg/ha of N (2358 and 7845 kg/ha) and 100 kg/ha of N in two equal splits for seed yield (2324 kg/ha) and 100 kg/ha of N in three splits for stover yield (7606 kg/ha).